Hexamethine hemicyanine dye as a thermo-optical probe for serum albumin. (November 2021) - Udayan, Sony; Elizebath, Drishya; Sherin, D.R.; Praveen, Vakayil K.; Sunny, Sini; Jayamurthy, Purushothaman; Manojkumar, T.K.; Nampoori, V.P.N.; Thomas, Sheenu
Highlights: The interaction of hemicyanine dye, LDS 821 with serum albumins was investigated using spectroscopic techniques. The CD studies revealed an increase in the α -helix content of proteins upon binding with the dye. Molecular docking studies of dye on serum albumins proved that the dye binds to interior of the serum albumins. The thermo-optical properties of the dye upon binding with proteins were studied using the thermal lens technique. The thermal diffusivity of dye showed a linear decrease with an increase in the concentration of serum albumins. Abstract: In the present work, we demonstrate the usefulness of a hexamethine hemicyanine dye as a thermo-optical probe for serum albumin, an abundant transport protein in the circulatory system, and its optimum concentration is often considered as an indicator of good health. For this purpose, the interaction of near-infrared (NIR) hemicyanine dye, LDS 821 (Styryl 9 M) with bovine serum albumin (BSA) and human serum albumin (HSA) has been investigated using various spectroscopic techniques and molecular docking method. The gradual red-shift in UV–vis absorption and an increase in the emission intensity of the hemicyanine dye upon incremental addition of serum albumin indicating the binding of the dye with the protein. The circular dichroism spectroscopy studies revealed an increase in the α -helix content of protein with an increase in dye concentration specifying enhanced stability of proteins upon binding with the dye. The results of these studies imply that binding of hemicyanine dye to the hydrophobic pockets of serum albumin considerably alters its optical properties by reducing the mobility and structural flexibility of the dye. Based on this understanding, thermo-optical properties of the dye in the absence and presence of serum albumin have been analyzed using a dual-beam mode matched thermal lens technique, which measures a rise in temperature due to the nonradiative relaxation of the excited state energy of the dye. A considerable decrease in the thermal diffusivity of the dye (1.39 × 10 −3 cm 2 /sec) in the presence of 0.1–0.7 μm HSA (1.30–0.99 × 10 −3 cm 2 /sec) and BSA (1.33–0.97 × 10 −3 cm 2 /sec) has been observed owing to the change in the heat diffusion capacity of the dye bounded with protein. The low fluorescence yield and the ability to bind in the interior of protein molecules make NIR emissive hemicyanine dye LDS 821 a potential thermo-optical probe for detecting serum albumin, an aspect unexplored for this class of dyes. The present study demonstrates that the thermal lens method with a suitable thermo-optical probe can be used as a sensing method for serum albumin.